Non Invasive Follicular Thyroid Neoplasm with Papillary Like Nuclear Features (NIFTP): A Case Report (Global Journal of Medical Research, 2018)
World health organization (WHO) 2017 fourth edition has introduced entity Non Invasive follicular thyroid neoplasm with papillary like nuclear features (NIFTP), which reflects indolent course of this tumor. NIFTP has an established diagnostic criteria including papillary like nuclear features and entire tumor capsule submission to exclude invasion. NIFTP shows RAS type mutation expressed by other follicular lesions. This nomenclature change with strict and reproducible diagnostic criteria will help to better guide the treatment and reduce the burden of over treatment.
Keywords: non invasive follicular thyroid neoplasm with papillary like nuclear features (NIFTP)